SOCIAL FUNCTIONING OF PATIENTS WITH SCHIZOPHRENIA IN SRI LANKA (Proceedings of the International Conference on Public Health, 2022)
The current study was the first large-scale study of the functioning level of SriLankan Schizophrenia / Psychotic patients and the first-ever study of this patientpopulation by a psychologist and therefore would shed light on the psychologicalperspectives on this population. Most judgments regarding the level of functioning ofschizophrenia patients are derived from Indian studies. India is Sri Lanka’s closestneighbor and therefore most Indian research assumptions are usually generalized to SriLanka. Yet the current study reports similarities as well as differences among Sri LankanSchizophrenia patients when compared to Indian patients. These differences are attributedto the different social composition of Sri Lanka compared to the Indian society, despite themany shared similarities of the two countries. Women appear to have better socialfunctioning compared to men. High rates of prosocial behavior and voting were observedin the sample. 77.5% of the sample reports never engaging in physical activities while 39.5% reports engaging in religious activities often. The study was conducted with a sample of200 out-patients (n=200) from the National Institute of Mental Health (NIMH), Sri Lanka.A translated, validated version of the Social Functioning Scale (SFS) was used in thestudy. A convenient sample was used.
Keywords: Sri Lanka, Social Functioning, Schizophrenia, Psychosis